Metabolic Profiling of Cannabis Secondary Metabolites for Evaluation of Optimal Postharvest Storage Conditions - Milay, Looz; Berman, Paula; Shapira, Anna; Guberman, Ohad; Meiri, David (Frontiers in Plant Science, 2020)
The therapeutic use of medical Cannabis is growing, and so is the need for standardized and therapeutically stable Cannabis products for patients. The therapeutic effects of Cannabis largely depend on the content of its pharmacologically active secondary metabolites and their interactions, mainly terpenoids and phytocannabinoids. Once harvested and during storage, these natural compounds may decarboxylate, oxidize, isomerize, react photochemically, evaporate and more. Despite its widespread and increasing use, however, data on the stability of most of the plant's terpenoids and phytocannabinoids during storage is scarce. In this study, we therefore aimed to determine postharvest optimal storage conditions for preserving the composition of naturally biosynthesized secondary metabolites in Cannabis inflorescences and Cannabis extracts. To this end, Cannabis inflorescences (whole versus ground samples) and Cannabis extracts (dissolved in different solvents) from (-)-Δ9-trans-tetrahydrocannabinol- or cannabidiol-rich chemovars, were stored in the dark at various temperatures (25, 4, -30 and -80 °C), and their phytocannabinoid and terpenoid profiles were analyzed over the course of one year. We found that in both Cannabis inflorescences and extracts, a storage temperature of 25 ºC led to the largest changes in the concentrations of the natural phytocannabinoids over time, making this the most unfavorable temperature compared with all others examined here. Olive oil was found to be the best vehicle for preserving the natural phytocannabinoid composition of the extracts. Terpenoid concentrations were found to decrease rapidly under all storage conditions, but temperatures lower than -20 ºC and grinding of the inflorescences were the least favorable conditions. Overall, our conclusions point that storage of whole inflorescences and extracts dissolved in olive oil, at 4 ºC, were the optimal postharvest conditions for Cannabis.